Remodeling tumor microenvironment with nanomedicines. (14th June 2021) - Martin, John D.; Miyazaki, Takuya; Cabral, Horacio
Abstract: The tumor microenvironment (TME) has been recognized as a major contributor to cancer malignancy and therapeutic resistance. Thus, strategies directed to re‐engineer the TME are emerging as promising approaches for improving the efficacy of antitumor therapies by enhancing tumor perfusion and drug delivery, as well as alleviating the immunosuppressive TME. In this regard, nanomedicine has shown great potential for developing effective treatments capable of re‐modeling the TME by controlling drug action in a spatiotemporal manner and allowing long‐lasting modulatory effects on the TME. Herein, we review recent progress on TME re‐engineering by using nanomedicine, particularly focusing on formulations controlling TME characteristics through targeted interaction with cellular components of the TME. Importantly, the TME should be re‐engineering to a quiescent phenotype rather than be destroyed. Finally, immediate challenges and future perspectives of TME‐re‐engineering nanomedicines are discussed, anticipating further innovation in this growing field. This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Abstract : Nanomedicines directed to re‐engineer the tumor microenvironment (TME) can reduce tumor malignancy and promote the delivery antitumor agents and cells to enhance antitumor efficacy. In this review, we present nanomedicine‐based strategies for remodeling tumor by controlling TME characteristics through targeted interaction with cellular components of the TME.